Fasies, lingkungan pengendapan dan sifat fisik (kesarangan dan kelulusan) batuan karbonat Formasi Parigi di daerah Pangkalan Karawang, Jawa Barat - Praptisih Praptisih (Jurnal Geologi dan Sumberdaya Mineral, 2016)
Parigi Formation carbonate rocks well croped out in the Pangkalan area, Karawang. Research methods include both of field research of detailed observations of Parigi Formation carbonate rocks and laboratory analysis consisting of petrography and paleontology. The results showed that the carbonate rock of the Parigi formation can be identified into seven facies carbonate namely (1) plangtonic packstone facies, (2) foraminiferal packstone facies, (3) packstone facies, (4) bindstone facies, (5) rudstone facies, (6) Framstone facies, and (7) algal-forams packstone facies. The Parigi Formation estimated deposited on the environments lower reef slope, reef front, reef crest and backreef. The results of the analysis of large foraminifera fossils show the age Parigi Formation is Early Miocene. The physical analysis showed that porosity and permeability founded in framestone facies, up to 25.84% and 21.13 mD permeability. From the pattern of depositional environment The Parigi Formation in the central basin that is probably is in the west-southwest area.Â Keywords: carbonate rocks, Parigi Formation, facies, depositional environments, reefs